Inertia in Infrastructure Development : Some Analytical Aspects, and Reasons for Inefficient Infrastructure Choices - Strand, Jon (2012)
This paper uses some simple conceptual models to draw out various implications of infrastructure investments with long lifetimes for the ability of societies to reduce their future greenhouse gas emissions. A broad range of such investments, related both to energy supply and demand systems, may commit societies to high and persistent levels of greenhouse gas emissions over time, that are difficult and costly to change once the investments have been sunk. There are, the author argues, several strong reasons to expect the greenhouse gas emissions embedded in such investments to be excessive. One is that infrastructure investment decisions tend to be made on the basis of (current and expected future) emissions prices that do not fully reflect the social costs of greenhouse gas emissions resulting from the investments. A second, related, set of reasons are excessive discounting of future project costs and benefits including future climate damages, and a too-short planning horizon for infrastructure investors. These issues are illustrated for two alternative cases of climate damages, namely with the possibility of a "climate catastrophe," and with a sustained increase in the marginal global damage cost of greenhouse gas emissions.